Documentary filmmaking in Iraqi satellite T.V channels (Journal of Imam Al-Kadhim College, 2024)
The documentary film is one of the types of media messages of importance from a scientific and practical point of view because of its features and characteristics such as realism, high credibility as well as public confidence Therefore, it used in different topics as political, military, economic, social, environmental, health and etc., for this employed the technical and human resources to produce high-quality documentary films. To convey the meaning whose sender want to the audience includes realities and facts as well as save it from losing, we notice there are some careless in interest in this media industry in Iraqi satellite television channels, which was reflected in the production of documentaries in quantity and quality.So here we can notice the problem of research, which is represented by the lack of interest in documentary filmmaking in Iraqi satellite television channels.Hence, the researcher starts the study of problem as he feels the importance of the documentary filmmaking and if its achieve tasks as professional especially toward national issues, including the large number of topics that need to be convey to public and documented.the researcher first began to review previous studies, books and researches and different information source about documentary films to form theoretical aspect of research, as the origin of documentary film, concept, types, its goals, then the researcher conducted a survey the audience of satellite television channels to measure their attitude toward what was shown of documentary films during 2023, and supported the study by meeting a group of documentary filmmakers, including writers, directors and production officials, to poll their opinions in the documentary filmmaking in Iraq and the most prominent challenges it faces, as well as representatives of television channels. The research reached a set of results, most notably:The results of the field study showed that satellite television channels did not give this media industry the size that is commensurate with its role and importance within the media messages addressed to the public, which was reflected in the decrease in the number of films watched by the sample members, as the results indicated that the Iraqi satellite television channels were selecting the topics of films according to their policies and agenda and not according to their societal importance, and media professionals cannot change the direction of the production compass, while the goals that they sought to achieve through documentary films were limited to propaganda goals and Political promotion mainly, while informational, educational and investigative objectives were less.
Keywords: Documentary film, Documentary filmmaking